Techno-economical feasibility study on the retrofit of double-ended Ro/Pax ferries into battery-powered ones - Bakirtzoglou, Christos (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Ναυτικής Μηχανολογίας, 2017)
Humanity by necessity is being forced to reduce its carbon footprint and invest in operations aimed at limiting emissions and improving resource efficiency in order to achieve sustainable growth. Air pollution and climate change are intertwined and they have also started occurring. Ports, coastal cities and their local communities are amongst the most vulnerable to extreme weather conditions resulting from them. The concept of the all‐electric‐ship seems to be the optimal solution from shipping sector. The all‐electric ship design which aims at supporting and promoting energy efficiency, if powered from electricity generated from renewable sources may claim to be a 100% zero‐emission transportation mean. Purpose of this thesis, therefore, is the techno‐economical feasibility investigation of the retrofit of existing small double‐ended ferries into battery powered‐ones, as it is stated in chapter one. It includes retrofit cost calculation, a comparison analysis of fuel and O&M savings on a year’s operation, shore side’s appropriate infrastructure and it’s arrangement, and externalities costs because of the emissions saved. In second chapter of the dissertation, an option analysis is offered under the target of a zero‐emissions vessel. Moreover, a brief historical guide to all‐electric ships, from their birth to nowadays is presented. Next chapter analyzes battery storage systems, their structure, their chemistry technologies and how to evaluate them for marine application use. Existing vessels’ under investigation main characteristics, machinery equipment and operational routine are described in the fourth chapter. Retrofit’s overview concerning vessels’ and shore’s basic machinery installations and modifications is described. Moreover, the legal and regulatory framework for launching an all‐electric ship and installing an onshore power supply system is outlined before proceeding into the technical design of the conversion. Chapter five describes the conceptual electrical topologies that can be applied on vessel and on shore side. Depending from vessel’s characteristics and power demands different configurations can be used for AC, DC distribution networks or LV, HV systems. Details for the interconnection system are reported, as well. The design methodology concerning the estimation of battery capacity required on‐board according to vessel’s operational profile and safety criteria is presented in chapter 6. A plexus of scenarios depending to operational characteristics, vessel’s currently installed power output, charging procedures and battery specifications is created in order to evaluate the significance of each parameter. Each scenario’s outcomes are the total number of batteries needed, their price, their weight and volume, and life expectancy. General design guidelines from methodology’s implementation are highlighted. Chapter seven discusses about air pollution and its multivariate impacts on flora and fauna, and its contribution to climate change. Tools for estimating the amount of pollutants which will be saved due to vessel’s retrofit are offered alongside. Moreover, externality cost values per tn of pollutant emitted are presented based on the impact pathway analysis. The retrofit electrification methodology is applied into a typical small double‐ended Ro/Pax ferry and the results are shown in chapter eight. In addition, according to the scenario selected system’s totalinstallation price and savings from fuel consumption are calculated. Financial and economical appraisal of the project is presented, including the externalities costs integration.